Association of the metabolic syndrome components with the chronotype, level of daytime sleepiness and dispositional optimism in patients with arterial hypertension - Khrystyna Novak-Mazepa; Mariya Marushchak; Tetiana Tomchuk; Olena Gashynska; Tetiana Pastryk (Journal of Health Sciences, 2023)
Introduction: Arterial hypertension (AH) coexists with such conditions as obesity, insulin resistance/hyperinsulinemia and dyslipidemia, that is, interrelated metabolic disorders that characterize the metabolic syndrome (MS). The aim of the study was to establish relationships between components of MS and chronotype, level of daytime sleepiness, and dispositional optimism in patients with AH.